2007
DOI: 10.1097/01.coc.0000231364.89294.13
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Ovarian Cancer and Low Malignant Potential (LMP) Tumors Associated With a Lower Incidence of Second Primary Breast Cancer

Abstract: Patients with a history of having either an LMP tumor or an epithelial ovarian cancer have a less than expected risk of subsequent breast cancer. Patients with LMP tumors are at lower risk than patients with a history of ovarian cancer for the development of these second malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…5 – 9 , 11 – 21 Most of these studies demonstrated an increased risk of SPM, 5 – 8 , 12 , 14 , 15 , 17 , 18 , 20 but others did not. 9 , 11 , 13 Bergfeldt et al 9 proposed that findings of increased occurrence of secondary primary cancer in patients with ovarian cancer have been biased by misclassification. A study conducted in the UK confirmed the high incidence of synchronous cancer in patients with ovarian cancer, which may also bias estimates of SPM incidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 – 9 , 11 – 21 Most of these studies demonstrated an increased risk of SPM, 5 – 8 , 12 , 14 , 15 , 17 , 18 , 20 but others did not. 9 , 11 , 13 Bergfeldt et al 9 proposed that findings of increased occurrence of secondary primary cancer in patients with ovarian cancer have been biased by misclassification. A study conducted in the UK confirmed the high incidence of synchronous cancer in patients with ovarian cancer, which may also bias estimates of SPM incidence.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Several studies have described an increased risk of secondary breast cancer after ovarian cancer, with a focus on invasive forms. 11 , 13 , 15 Several possible explanations may be offered for the increased risk of SPM after ovarian cancer. First, an inherent or acquired defect of tumor suppressor genes or DNA repair genes may induce such cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported significantly higher relative risks of second primary cancers subsequent to ovarian cancer, such as colorectal cancer, 8‐12 breast cancer, 8,9,11,12 bladder cancer, 8‐12 and leukemia, 8‐10,12,13 probably due to common etiology, hereditary factors and chemotherapy‐induced secondary malignancies. Few studies, however, have examined relative risks of cancer following BOTs 14‐17 . One study found no increased relative risk of cancers, 17 whereas two studies reported significantly elevated risks of ovarian 16 and colorectal cancer 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for the 20% of OECs that express little or no CA125, a single marker is not sufficient. In particular, HE4 levels are elevated in more than 50% of tumours that do not express CA125 [42]. Therefore, the addition of HE4 to CA125 allows detecting malignancies in patients with tumours that do not express CA125 and will be missed by algorithms using CA125 alone.…”
Section: Roma Algorithmmentioning
confidence: 99%